1987
DOI: 10.1093/oxfordjournals.eurheartj.a062268
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting coronary vasodilatory action of the molsidomine metabolite Sin I: a quantitative angiographic study

Abstract: The vasodilatory action of molsidomine was studied by intracoronary injection of its active metabolite, Sin 1. In 10 patients repeat coronary angiography in multiple projections was performed before and 2 minutes after administration of 1 mg of Sin 1, and before and after a second injection 60 minutes later. Contours of obstructed and non-obstructed segments of the left coronary artery were quantitatively analysed with a computer-based angiography analysis system. Immediately after its administration, Sin 1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Surprisingly, we did not observe a significant alteration of blood flow velocities as measured by TCD, which we had expected as a potential side effect of molsidomine on the cerebral conductive vasculature. 25,27 The beneficial effect of molsidomine treatment on clinical outcome could be explained by its NO-related protective effect on the brain rather than as a therapeutic effect on vasospasm of the conductive vessels. This confirms the findings from the recently published cilostazol trial, in which an endothelial protective effect is attributed to elevating intracellular NO levels through the inhibition of phosphodiesterase 3 by using cilostazol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we did not observe a significant alteration of blood flow velocities as measured by TCD, which we had expected as a potential side effect of molsidomine on the cerebral conductive vasculature. 25,27 The beneficial effect of molsidomine treatment on clinical outcome could be explained by its NO-related protective effect on the brain rather than as a therapeutic effect on vasospasm of the conductive vessels. This confirms the findings from the recently published cilostazol trial, in which an endothelial protective effect is attributed to elevating intracellular NO levels through the inhibition of phosphodiesterase 3 by using cilostazol.…”
Section: Discussionmentioning
confidence: 99%
“…7 An alternative NO donor with more favorable pharmacodynamic and pharmacokinetic profiles and less toxicity is molsidomine, a standard treatment for heart failure and coronary heart disease. 25,27 Thus, in this study, we used intravenously administered molsidomine as a rescue therapy in SAH patients with established CVS and observed its effect on the occurrence of DINDs, vasospasm-related infarcts, and clinical outcome.…”
mentioning
confidence: 99%
“…Direct myocardial invasion by cardiotropic virus rapidly progress to the second phase of immunologic activation. The use of immunosuppression during acute viral myocarditis remains controversial3, 4). Lernel5-7) suggested that steroids be avoided at least during the first 10 days of acute infection because steroids inhibit interferon synthesis and increase viral multiplication in experimental coxsackievirus infection.…”
Section: Introdctionmentioning
confidence: 99%
“…The damage to the myocardium in AFM may be mediated by predominantly immunological mechanisms rather than by the direct effect of viral infection and replication (13,14). Previous studies have indicated the therapeutic effects of the IVIG in acute myocarditis (11,15).…”
Section: Discussionmentioning
confidence: 99%